Levantamento de artrópodes-pragas e inimigos naturais na produção de citros de mesa em sistema de cultivo protegido - Freitas, Mickael Lombardi de (Universidade Federal de São Carlos, 2025)
This study addresses the survey of arthropod pests and natural enemies in citrus fresh fruit production in a protected cultivation system, as an alternative to combat Huanglongbing - HLB, associated with the bacterium Candidatus Liberibacter asiaticus, by avoinding it´s vector, the Diaphorina citri psilld. The experimental and demonstrative module of the system was installed at the Sylvio Moreira Citrus Center - IAC, Cordeirópolis - SP, in 2015, evaluating the screen and plastic covers and the canopy varieties Clementina, Charmute de Brotas, Pera IAC, Ponkan, Dekopon, Seleta do Rio, Navelina and Baianinha, grafted on the rootstock Poncirus trifoliata var. monstrosa (‘Flying Dragon’). Maximum and minimum temperatures were monitored weekly with the aid of meteorological stations (WD) and light intensity was monitored through lux meters installed in both environments. Pest assessments were performed by visual inspections, carried out every 15 days, following the design of subdivided plots with environments (plastic and screen covering) in the plots and position of the environment (north and south) in the subplots. Monthly evaluation of yellow traps was performed from January to June, with the aim of characterizing qualitatively (species present) and quantitatively (number of individuals collected) in each environmental condition. Yellow sticky traps were installed at 37 points, distributed in the environments with plastic and screen covering and changed monthly. Biweekly visual inspections of pests were also performed. The massive presence of whitefly (Aleurothrixus floccosus) was observed, with greater occurrence in the screen covered ambient. In addition to this, the other pest species with the highest occurrence were thrips (Frankiniella sp.), citrus leafminer (Phyllocnistis citrella) and fruit fly (Ceratitis capitata). Regarding natural enemies, the absence of leafminer (Chrysoperla spp.) and ladybugs (Coleoptera: Coccinellidae), which are predators of citrus pests, was observed both in visual inspection and in trap evaluation. Additionally, specimens of microhymenoptera, known parasitoids of pest insects, were observed.
Survey of arthropod pests and natural enemies in greenhouse citrus production system
Keywords: Huanglongbing; Levantamento; Inimigos naturais; Pragas; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE